A Conceptual Framework for Hospital Outdoor Landscape Designs from Theoretical to Practical Levels (A Systematic Literature Review and Content Analysis) - Naeimeh Asadian Zargar; Kianoush Suzanchi; Mohammad Mehdi Sepehri (منظر, 2023)
Despite numerous studies on how the hospital outdoor landscape affects user satisfaction and the publication of design guidelines, this field’s research flow, strengths, and weaknesses have not been thoroughly reviewed. This makes it difficult for designers to access organized information on design’s theoretical and practical aspects. The current research aims to comprehensively review and analyze the existing resources and present them in a conceptual framework. This process will enable us to identify the strengths and weaknesses of the current literature and identify specific areas that require further research in the field of hospital landscape design. After conducting a systematic review, 47 relevant sources were identified. These sources were then analyzed using the content analysis method and encoded in MAXQDA software to organize the obtained information. 618 codes were extracted and categorized into six main categories and 30 subcategories. These categories form the conceptual framework of hospital outdoor landscape design literature, covering topics such as 1) definitions of hospital outdoor landscape, 2) typology, 3) fundamental theories, 4) design approaches, 5) principles and design indicators, and 6) preferences and needs of users. Based on the research, the literature in this field has been developed appropriately from both theoretical and practical perspectives (i.e., programming and operational dimensions). The theoretical essence of hospital outdoor landscapes is evolving. It can now be defined as a space that serves functional and symbolic purposes while providing a sense of restoration. To describe the objective dimension of the landscape, typological studies have been conducted. The literature on designing hospital outdoor landscapes from a practical perspective initially focused on design approaches that aimed to implement their expected functions. These approaches may vary in principles, methods, and actions, but their main objective is to elucidate the interaction between the hospital landscape and its users. The principles, qualities, and recommendations are general and applicable to various users, making them suitable for public hospitals. The main weakness of hospital outdoor landscape literature is the lack of reliable evidence concerning the users’ perception and interaction with the environment. To address this, it is crucial to conduct evaluation studies on various case samples in different settings to improve the quality of the literature.